Validating Plant Genes Involved in Pepper Yellow Leaf Curl Indonesia Virus Infection Using VIGS in Model Plant Nicotiana benthamiana - Masanori Kaido; Kazuyuki Mise; Kusumawaty Kusumanegara (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2020)
Pepper yellow leaf curl disease caused by Pepper yellow leaf curl Indonesia virus (PepYLCIV) has become a challenge to chili pepper cultivation. Development of resistant variety by utilizing recessive resistance gene is expected to control the disease in the field. This study aimed to validate three plant genes, namely deltaCOP, hsc70, and BAM1, in PepYLCIV infection by applying Virus-induced Gene Silencing (VIGS) in a model plant, wild type Nicotiana benthamiana. PepYLCIV and construct of Tobacco rattle virus (TRV) which induced silencing of each gene were co-inoculated into N. benthamiana plants through agroinfiltration. Gene expression and the relative amount of viral DNA were determined by quantitative reverse transcription PCR (qRT-PCR) and quantitative PCR (qPCR), respectively, at 15 days post inoculation. The results showed a decreased level of deltaCOP, hsc70, and BAM1 expressions to 66.4%, 53.0%, and 47.0%, respectively, compared to that in the control (100%). Silencing of the three genes decreased the accumulation of PepYLCIV to 0.1%, 18.4%, and 63.0%, respectively, compared to that in the control. deltaCOP and hsc70 genes were indicated to be involved in the viral infection and could be good candidate genes for obtaining chili pepper varieties resistant to PepYLCIV. This result affirmed that the reverse genetics technique could be an alternative approach for identifying plant genes involved in viral infection, including PepYLCIV. The use of an infectious clone in this study allows the virus inoculations could be carried out without rearing and maintaining its natural vector, hence reduces the risk of virus transmission to healthy plants.